Alcohol-related risk and harm amongst young offenders aged 11-17. Issue 2 (15th June 2015) - Newbury-Birch, Dorothy; Jackson, Katherine; Hodgson, Tony; Gilvarry, Eilish; Cassidy, Paul; Coulton, Simon; Ryan, Vicky; Wilson, Graeme B.; McGovern, Ruth; Kaner, Eileen
Abstract : Purpose: – The purpose of this paper is to examine the prevalence of alcohol use disorders (AUDs) amongst young people in the criminal justice system (CJS) in the North East of England and to compare the ability of the Alcohol Use Disorders Identification Test (AUDIT) to the Youth Justice Board ASSET tool in identifying alcohol-related need in Youth Offending Team (YOT) clients. Design/methodology/approach: – A validated screening tool (AUDIT) was used to identify alcohol-related health risk or harm. Findings from AUDIT were compared with those of the standard criminogenic risk screening tool used in CJS (ASSET). An anonymous cross-sectional questionnaire was administered during a one-month period in 2008. The questionnaires were completed by 11-17-year-old offenders who were in contact with three YOTs, one Youth Offending Institution and one Secure Training Estate. Findings: – In total, 429 questionnaires were completed out of a possible 639 (67 per cent). The majority (81 per cent) of the young offenders were identified as experiencing alcohol-related health risk or harm and 77 per cent scored within a possibly alcohol-dependent range. In total, 77 (30 per cent) of young people completing both assessments were identified as having an AUD by AUDIT but not identified as needing alcohol-related treatment using ASSET. Research limitations/implications: – This research was confined to one geographical area of England, however, the results show that even in this area of high drinking by young people the levels of AUDs amongst young people in the CJS are very high. Social implications: – There are major social implications to this research. It is imperative for changes to be made to the care pathways in place in the UK for young people coming through the CJS with alcohol-related issues. Originality/value: – This paper adds to the evidence base by using well-validated tools to measure alcohol use amongst young people in the CJS in the UK.